The Hudson Collection [large type] - Green, Jocelyn (Green, Jocelyn. On Central Park, 2024)
"Elsa Reisner's lifelong dream of working as an ornithologist at the American Museum of Natural History is fading as the job begins to drain her passion. But fate takes an unexpected turn when she is assigned to catalog the bequest of a recently deceased patron whose Gothic country mansion holds secrets and treasures waiting to be discovered. As Elsa delves into her task, she forms an unlikely bond with the estate's delightful gardener and her daughter, as well as an architectural salvage dealer who still bears scars from the Great War. Together, they embark on a thrilling treasure hunt for a missing relic intended to safeguard the servants' futures before the estate is sold. At the same time, Elsa's body seems to betray her with new symptoms from a childhood disease that isn't through with her yet. With the brooding veteran and her handsome colleague joining the search, Elsa must navigate the tangled web of secrets and hidden motives along with the changing state of her health. As her deadline looms ever closer, will she be able to secure a new life for her friends before the estate slips from their grasp?"--